Effects of entresto on ejection fraction, and the effects of selected demographic and clinical variables, and the effects titrated entresto dose on ejection fraction. - Mooney, Mary (European Society of Cardiology, 2024)
Administration of Entresto made a positive difference to the EF. Age, myocardial infarction history, pre Entresto EF, and maximum dosage of (97/103) were significantly associated with the output variables. Where possible, rapid up-titration should be aimed for. Larger studies would help identify additional predictors.
Book of Abstracts, ESC
European Society of Cardiology, Heart Failure Congress
PUBLISHED
Lisbon
Keywords: Chronic Illness self-management